2006
DOI: 10.1177/0969733006069696
|View full text |Cite
|
Sign up to set email alerts
|

Competent Patients’ Refusal of Nursing Care

Abstract: Competent patients' refusals of nursing care do not yet have the legal or ethical standing of refusals of life-sustaining medical therapies such as mechanical ventilation or blood products. The case of a woman who refused turning and incontinence management owing to pain prompted us to examine these situations. We noted several special features: lack of paradigm cases, social taboo around unmanaged incontinence, the distinction between ordinary versus extraordinary care, and the moral distress experienced by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…) and exercises autonomy as freedom of choice based on participation. Non‐compliance was described as an unusual expectation in nursing culture, where patients by habit frequently consented to nursing care irrespective of verbal or written consent (Dudzinski & Shannon ). Non‐compliance was defined as a patient's informed refusal of ordinary nursing care and could involve a lack of cooperation in nursing care activities, such as bladder or bowel management, even though such care provision was well known to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…) and exercises autonomy as freedom of choice based on participation. Non‐compliance was described as an unusual expectation in nursing culture, where patients by habit frequently consented to nursing care irrespective of verbal or written consent (Dudzinski & Shannon ). Non‐compliance was defined as a patient's informed refusal of ordinary nursing care and could involve a lack of cooperation in nursing care activities, such as bladder or bowel management, even though such care provision was well known to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 However, negotiation has been proposed as a method of dealing with patients who refuse treatment. 17 This technique enables health care providers to reach a compromise with patients without affecting their sense of autonomy. In our case, the patient agreed to a low-dose morphine infusion after major efforts by our team to educate and counsel her.…”
mentioning
confidence: 99%
“…Dudzinski & Shannon (2006) talk about a "negotiated reliance response" which they suggest may alleviate distress for practitioners. This involves discussions between all stakeholders, including the patient's family when appropriate; to facilitate a coordinated plan that recognizes the desires of all parties.…”
Section: A Collaborative Approachmentioning
confidence: 99%
“…Disrespectful care delivery by other practitioners (Nordam et al, 2005), maintaining client confidentiality (Solum & Schaffer, 2003) , a patient's refusal of care deemed appropriate by nursing staff (Dudzinski & Shannon, 2006), and patient autonomy in decision making (Brazil et al, 2010) were identified as significant elements of job demands contributing to moral distress. Moral distress has also been linked to overly aggressive or futile care situations (Brazil et al, 2010;Epstein, 2010;Ferrell, 2006;Kain et al, 2009;Oberle & Hughes, 2001; E. Rice et al, 2008).…”
Section: Site Specificmentioning
confidence: 99%
See 1 more Smart Citation